Psychological Impact of Renewable Energy Initiatives on Sustainable Practices in Sports Industries: A Comparative Analysis of Japan and Ningxia - REBIYA; Bingchan Xue; Jiehua Zhong; Zhijun He; Jie Chen, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Japan, as the world's third-largest economy, has made significant strides in balancing energy consumption with ecological conservation, despite its limited natural resources. This paper explores Japan's successful strategies in energy efficiency and pollution minimization, particularly in light of the technological advancements post-Tokyo Conference. It draws parallels between Japan’s energy policies and the challenges faced by the coal mining industry in Ningxia, emphasizing the psychological and behavioral shifts necessary for adopting renewable energy sources and enhancing carbon emission efficiency. The study reviews Japan's experience in implementing energy conservation measures and its achievements in green technology, applying these insights to the context of Ningxia’s coal mining practices. Four strategic experiences are discussed: conducting targeted research on green coal mining technologies, enhancing legal frameworks, innovating in green mining technology, and bolstering financial support for sustainable practices. This paper suggests that integrating these strategies can inspire a shift towards more sustainable, low-carbon practices in sports industries and beyond, promoting a broader cultural and psychological adoption of green development principles.